Child Growth According to Maternal and Child HIV Status in Zimbabwe. Issue 9 (September 2017) - Omoni, Adetayo O.; Ntozini, Robert; Evans, Ceri; Prendergast, Andrew J.; Moulton, Lawrence H.; Christian, Parul S.; Humphrey, Jean H.
Abstract : Background: Growth failure is common among HIV-infected infants, but there are limited data on the effects of HIV exposure or timing of HIV acquisition on growth. Methods: Fourteen thousand one hundred ten infants were enrolled in the Zimbabwe Vitamin A for Mothers and Babies trial in Zimbabwe before the availability of antiretroviral therapy or co-trimoxazole. Anthropometric measurements were taken from birth through 12–24 months of age. Growth outcomes were compared between 5 groups of children: HIV-infected in utero (IU), intrapartum (IP) or postnatally (PN); HIV-exposed uninfected (HEU); and HIV unexposed. Results: Growth failure was common across all groups of children. Compared with HIV-unexposed children, IU-, IP- and PN-infected children had significantly lower length-for-age and weight-for-length Z scores throughout the first 2 years of life. At 12 months, odds ratios for stunting were higher in IU [6.25, 95% confidence interval (CI): 4.20–9.31] and IP infants (4.76, 95% CI: 3.58–6.33) than in PN infants (1.70, 95% CI: 1.16–2.47). Compared with HIV-unexposed infants, HEU infants at 12 months had odds ratios for stunting of 1.23 (95% CI: 1.08–1.39) and wasting of 1.56 (95% CI: 1.22–2.00). Conclusions: HIV-infected infants had very high rates of growth failure during the first 2 years of life, particularly if IU or IP infected, highlighting the importance of early infant diagnosis and antiretroviral therapy. HEU infants had poorer growth than HIV-unexposed infants in the first 12 months of life.